Entrepreneurship, foreign direct investments and economic wealth in Africa - Daniel Ofori-Sasu; Smile Dzisi; Joshua Yindenaba Abor (Cogent Business & Management, 2023)
The paper seeks to examine the joint effect of entrepreneurship and FDI inflows on economic wealth in Africa. It employs a dynamic system GMM for a panel dataset of 52 African economies between 2006 and 2020. The study finds that FDI inflows induced a negative impact on the ease of doing business but it increases the business capital start-ups of entrepreneurs. We find that entrepreneurship reduces economic wealth in the short term but in the long-term entrepreneurship positively affect economic wealth. The results show that FDI inflows increase economic wealth and that FDI is an important channel through which entrepreneurship can impact economic wealth. We find evidence to support that ease of doing business and FDI inflows are substitutes while minimum capital of starting business complements FDI inflows in determining economic wealth. Based on the marginal effects, we conclude that entrepreneurship reduces economic wealth but improves economic wealth when the level of FDI inflows increases in a country. The implication is that countries should provide strategies that promote economic wealth of individuals, people and entrepreneurs through prudent business development framework and FDI supports in the short term.
Keywords: 650; economic wealth; Entrepreneurship; FDI inflows